Chemical Oscillation and Morphological Oscillation in Catalyst-Embedded Lyotropic Liquid Crystalline Gels - Li, Guanying; Cortes, William; Zhang, Qizheng; Zhang, Ye (Frontiers in Chemistry, 2020)
Liquid crystalline gels offer promising means in generating smart materials due to programmable mechanics and reversible shape changes in response to external stimuli. We demonstrate a simple and convenient method of constructing catalyst-embedded lyotropic liquid crystalline (LLC) gels and achieve chemomechanical oscillator by converting chemical waves in Belousov–Zhabotinsky (BZ) reaction. We observe the directed chemical oscillations on LLC sticks accompanied by small-scale oscillatory swellings–shrinkages that are synchronized with the chemical waves of an LLC stick. To amplify the mechanical oscillations, we further fabricate small LLC fibers and achieve macroscopically oscillatory bending–unbending transition of the LLC fiber driven by a BZ reaction.